Ecology, morphology and anatomy of Aldrovanda vesiculosa L. (Droseraceae) from Bangladesh (Bangladesh Journal of Botany, 2011)
Ecology, morphology and anatomy of Aldrovanda vesiculosa L. collected from Chalan beel wetland of Rajshahi district in 1987 have been studied. An illustrated account is presented with a review of literature. Key words: Aldrovanda vesiculosa L.; Carnivor; Ecology; Morphology; Bangladesh DOI: http://dx.doi.org/10.3329/bjb.v40i1.8002 Bangladesh J. Bot. 40(1): 85-91, 2011 (June)